Risk of miscarriage with bivalent vaccine against human papillomavirus (HPV) types 16 and 18: pooled analysis of two randomised controlled trials. (2nd March 2010) - Wacholder, Sholom; Chen, Bingshu Eric; Wilcox, Allen; Macones, George; Gonzalez, Paula; Befano, Brian; Hildesheim, Allan; Rodríguez, Ana Cecilia; Solomon, Diane; Herrero, Rolando; Schiffman, Mark
Abstract : Objective To assess whether vaccination against human papillomavirus (HPV) increases the risk of miscarriage. Design Pooled analysis of two multicentre, phase three masked randomised controlled trials Setting Multicentre trials in several continents and in Costa Rica. Participants 26 130 women aged 15-25 at enrolment; 3599 pregnancies eligible for analysis. Interventions Participants were randomly assigned to receive three doses of bivalent HPV 16/18 VLP vaccine with AS04 adjuvant (n=13 075) or hepatitis A vaccine as control (n=13 055) over six months. Main outcome measures Miscarriage and other pregnancy outcomes. Results The estimated rate of miscarriage was 11.5% in pregnancies in women in the HPV arm and 10.2% in the control arm. The one sided P value for the primary analysis was 0.16; thus, overall, there was no significant increase in miscarriage among women assigned to the HPV vaccine arm. In secondary descriptive analyses, miscarriage rates were 14.7% in the HPV vaccine arm and 9.1% in the control arm in pregnancies that began within three months after nearest vaccination. Conclusion There is no evidence overall for an association between HPV vaccination and risk of miscarriage. Trial registration Clinical Trials NCT00128661 and NCT00122681 .